Nirmala Varmā ke sāhitya meṃ nārī - Siṃha, Ṭhākura Vijaya (Samatā Prakāśana, 2007)
Study of women character in the works of Nirmal Verma, 1929-2005, Hindi author
Includes bibliographical references (p. [208]-216). - Hindi in Devanagari-Schr
Keywords: Verma; Nirmal 1929-2005; Women in development